Association Between Helicobacter pylori Infection and Ulcerative Colitis: A Meta-Analysis Study - Mauna, Alesia Prillya; Simadibrata, Marcellus (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Ulcerative colitis (UC), a chronic inflammatory disease that can cause bloody diarrhea, remains a major global disease burden. While Helicobacter pylori infection is postulated to be able to reduce the occurrence of UC, its role in the disease itself remains contentious. Hence, this meta-analysis aims to examine whether H. pylori infection can lower the chance of developing UC.Method: A systematic search was conducted through three electronic databases, namely Cochrane, PubMed, and Embase, with the addition of individual hand searching to analyze the association between ulcerative colitis and H. pylori infection in the adult population. Relevant articles selected through eligibility criteria were assessed for quality by using the Newcastle-Ottawa Scale. Furthermore, a random-effects meta-analysis was conducted to estimate the pooled odd ratios (ORs) along with their 95% confidence intervals (CIs). Higgins test  and funnel plots were also conducted.Results: A total of 11,498 patients with UC and 356,130 controls from 22 studies were included in the meta-analysis. Included studies showed fair or good quality. Good quality was achieved with the minimum score of 3 stars for selection, 1 star for comparability, and 2 stars for outcome/exposure, while fair quality was achieved with the minimum score of 2 stars for domain, 1 star for comparability, and 2 stars for outcome/exposure. Our findings indicated that H. pylori infection was associated with lower odds of UC [pooled ORs 0.51 (95% CI: 0.46-0.56)]), albeit moderate heterogeneity (I2= 54%, p = 0.002). Furthermore, publication bias was not found.Conclusion: The present study adds to the growing body of evidence supporting the potential protective effects of H. pylori infection on the occurrence of UC. However, further primary research with prospective study design needs to be conducted to confirm our findings.